Exploring E-Commerce: Social Media’s Impact on Brand Awareness and Loyalty for Micro Businesses in Central Java - Ilham Akbar; Syafiq Mahmadah Hanafi; Abdul Mujib (UIN Sunan Gunung Djati, 2024)
This research aims to determine the role of social media in influencing the development of brand awareness and consumer loyalty for micro-businesses in the e-commerce sector. Using a quantitative approach, a survey was conducted on 268 micro business owners who use Instagram in Central Java. Analysis was conducted through structural equation modeling to explore the relationship between the intensity and effectiveness of social media marketing, brand awareness, and consumer loyalty. The findings show that both the intensity and effectiveness of social media marketing have a significant impact on brand awareness, which in turn affects consumer loyalty. This research also identifies the direct influence of social media marketing on consumer loyalty, compared to its influence through brand awareness. The results of this study demonstrate the importance of strategic engagement on social media for e-commerce micro businesses, emphasizing that the quality of engagement is more important than its frequency. This study provides insight into how micro-businesses with limited resources can leverage social media to gain a competitive advantage in the e-commerce sector.